DEVELOPMENT OF MOBILE WEB APPLICATIONS TO IMPROVE ACCESS TO INFORMATION AND SERVICES (CASE STUDY: PEKON TANJUNG REJO) - Joni; Ricco Herdiyan Saputra; Lucy Asiyani; Dita Novitasari (Asia Information System Journal, 2025)
The management of information and public services at the pekon level is still largely manual, resulting in delays, inefficiencies, and limited access for the community. This research aims to design and develop a mobile web application that supports improving access to information and administrative services in Pekon Tanjung Rejo. The methods used include needs studies through observation of service processes and interviews with pekon officials and residents, system design using the UML approach, implementation using PHP, Bootstrap, and XAMPP, and functional testing using the black-box method. User Acceptance Testing was conducted on eight participants consisting of three pekon officers and five residents as representatives of end users. The results of the development resulted in four main modules, namely the pekon information page, the administrative dashboard, the community contact feature through the Sapa Village menu, and the officer management module. Functional testing shows that all core functions including authentication, data management, and information delivery are running as specified. User acceptance tests show that the application interface is considered easy to understand, and supports accelerating access to information by the public. However, several obstacles were found, such as limited internet connectivity in certain regions and variations in users' digital literacy that affect the optimal use of applications. This study recommends improving connection stability, improving notification features, and long-term evaluation to assess the impact of applications on the effectiveness of public services at the pekon level.